2018
DOI: 10.1177/0361198118798988
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Vehicular Emission Impact of Nighttime Construction with VISSIM and Different MOVES Emission Estimation Approaches

Abstract: Shifting work zones from daytime to nighttime is a potential solution to air quality issues on roadway with high traffic volume and where it is undesirable to close lanes during peak hours. The expected benefit of such shifting is to reduce total fuel consumption and on-road vehicle emissions. However, the magnitude of emission reductions and air quality impacts has not been examined comprehensively at work zones. The study presented in this paper investigated the traffic-related emission impacts of work zones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Vlieger et al studied the influence of driving behavior and traffic conditions on fuel consumption and emissions for a small test fleet of passenger cars; city traffic was found to have the highest fuel consumption and emissions [ 11 ]. Gu et al investigated the traffic-related emission impacts of work zones using an urban freeway case study; a VISSIM test bed combined with the Environmental Protection Agency’s MOVES emission model was used to estimate the total emissions assuming daytime and nighttime lane-closure scenarios [ 12 ]. You et al explored the relationship between the horizontal curve radius and carbon dioxide emissions on freeways from field tests under real world driving conditions through the development of an emission factor model (EFM) [ 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vlieger et al studied the influence of driving behavior and traffic conditions on fuel consumption and emissions for a small test fleet of passenger cars; city traffic was found to have the highest fuel consumption and emissions [ 11 ]. Gu et al investigated the traffic-related emission impacts of work zones using an urban freeway case study; a VISSIM test bed combined with the Environmental Protection Agency’s MOVES emission model was used to estimate the total emissions assuming daytime and nighttime lane-closure scenarios [ 12 ]. You et al explored the relationship between the horizontal curve radius and carbon dioxide emissions on freeways from field tests under real world driving conditions through the development of an emission factor model (EFM) [ 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the desired speed distributions (40) for MLs and GPLs are calibrated and validated by field measured travel time values (36,41). Florence and Guo (36) performed an empirical study to collect acceleration profiles of random vehicles and revealed that for more realistic performance measurements the default VISSIM desired acceleration function needs to be calibrated, especially when researchers try to simulate a network with stop-and-go traffic or for emission effect study (42). Nevertheless, this study modeled CV internally.…”
Section: Vissim Simulation Networkmentioning
confidence: 99%
“…As mentioned earlier, collecting enough local vehicle trajectory data is expensive and time-consuming. Collecting data by simulation has also been used for emission estimates (6)(7)(8). However, the accuracy of the simulation data in reflecting real-world driving conditions was questioned (9).…”
Section: Literature Reviewmentioning
confidence: 99%